Intestino médio do diplópodo Urostreptus atrobrunneus: Estrutura, função e redefinição das células hepáticas - Moreira-de-Sousa, C. [UNESP]; Iamonte, M. [UNESP]; Fontanetti, C. S. [UNESP] (FapUNIFESP (SciELO), 2017)
Diplopods are considered important macroarthropods the soil as part of its maintenance and balance. These animals usually do not occur in high densities, but population explosions caused by environmental disturbances, climate changes, and use of pesticides that eliminate possible competitors, have been reported. The millipede Urostreptus atrobrunneus Pierozzi and Fontanetti, 2006 have become a nuisance to humans in infestation sites in urban centers of the state of Sao Paulo, Brazil. As a contribution to the understanding of this potential pest, this study describes the histology, histochemistry, and ultrastructure of the U. atrobrunneus midgut, and presents the redefinition of hepatic cells somewhat controversial in the literature. The region of the midgut is characterized by the absence of a cuticular intima, and composed of a pseudostratified epithelium on a thick basal membrane, followed by a muscle layer, a layer of hepatic cells, lined by an external membrane. The morphology observed in U. atrobrunneus is similar to that reported for other species of diplopods. The hepatic cells have been previously described as randomly without forming a layer, however, the present results clearly demonstrate that these cells form a continuous layer over the whole midgut.
Midgut of the diplopod Urostreptus atrobrunneus: Structure, function, and redefinition of hepatic cells
Keywords: Digestive tract; Diplopoda; Histochemistry; Histology; Ultrastructure